2015
DOI: 10.1097/qad.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HBV-active HAART regimens in an HIV–HBV multinational cohort

Abstract: Objectives To explore factors associated with short and long-term HBV DNA suppression in a multinational cohort of HIV-HBV co-infected subjects receiving HBV-active antiretrovirals. Methods 115 HIV-HBV co-infected subjects participating in one of two global ACTG randomized clinical trials of different antiretroviral regimens received either HBV-monotherapy with either lamivudine or emtricitabine (N=56) or HBV-dual therapy with TDF plus lamivudine or emtricitabine (N=59). Associations of pre-treatment charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…This finding is similar to other developing countries where 30 to 50% had baseline HBV DNA <20,000 IU/ml 6, 15, 18 . It is in these people with HBV DNA < 20,000 IU/ml that our study demonstrates >95% HBV suppression rates for 48 weeks in both the 3TC and the TDF+3TC HIV/HBV co-infected groups.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is similar to other developing countries where 30 to 50% had baseline HBV DNA <20,000 IU/ml 6, 15, 18 . It is in these people with HBV DNA < 20,000 IU/ml that our study demonstrates >95% HBV suppression rates for 48 weeks in both the 3TC and the TDF+3TC HIV/HBV co-infected groups.…”
Section: Discussionsupporting
confidence: 89%
“…Our multivariable analysis demonstrates that TDF is associated with HBV DNA suppression when HBV DNA ≥ 20,000 IU/ml (Table 2) or when HBeAg is negative (Supplementary Table S2) at baseline. In a recent multicenter study, Thio et al reported that in subjects with baseline HBV DNA <20,000IU/ml, monotherapy (3TC or FTC) and dual therapy (TDF+3TC or FTC) had similar efficacy in terms of HBV DNA suppression during 144 weeks of follow-up 15 . Taken together, these studies suggest that 3TC-based monotherapy might be considered in patients with HBV DNA <20,000 IU/ml or HBeAg negative when TDF cannot be safely used or accessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HBV‐DNA viral loads and transaminase levels were for the most part low at treatment initiation. These conditions might have been ideal to abate the emergence of LAM resistance and have appeared to be associated with low LAM resistance rates in other treated, co‐infected populations from SSA . Considering that only one patient in this study had LAM resistance, there was an insufficient number of events to appropriately address this question.…”
Section: Discussionmentioning
confidence: 98%
“…Contributing factors to renal impairment are the high rate of patients with hypertension and diabetes mellitus, as well as co-infections [ 10 ] and chronic use of nephrotoxic drugs such as tenofovir disoproxil fumarate (TDF), atazanavir/ritonavir (ATV/r), and lopinavir/ritonavir (LPV/r) [ 11–13 ]. TDF is widely used in SSA as a first line ART due to its high efficacy and low side effects and its simultaneous effect against hepatitis B infection [ 14 , 15 ].…”
mentioning
confidence: 99%